Surdez no contexto da educação matemática: um estudo sobre o conjunto dos números reais a partir de registros de representação semiótica e o tangram - Souza, Lucas José de (2019)
The present research aims to investigate the mobilization of registers of semiotic representation related to real number set, for such deaf students from freshman year at a bilingualism high school performed mathematics activities encompassing the tangram as a manipulable material. Within this scope, this research is underpin as a qualitative case study (YIN, 2005; LUDKE; ANDRÉ, 1987), theoretically built upon registers of semiotic representation (DUVAL, 2003; 2009; 2011; 2012a; 2012b). Data analysis encompasses observing classes, drawing up participants profile, developing an Exploratory Activity and dynamizing an Activities Sequence, which was filmed. Seven activities compose such sequence, which includes tangram so to spawn figural registers of its geometrical shapes. This leads to mobilization of mathematical object real numbers, once relationships between area and length measure are analyzed in pieces of the didactic resource. As results, iconic representations consolidated mobilization of other semiotic systems, mainly numerical representations in fraction form and irrational numbers. Such systems were articulated to geometric representations in number line and numerical representations in decimal form, besides representations in percentage form for rational numbers. Therefore, the didactic resource contributed in the learning of mathematical concepts by access to the object through a representation diversity, in which Brazilian Sign Language took center stage. Regarding this language, there is a shortage of mathematical signs, leading to their creation within the present research topic.